2019
DOI: 10.1371/journal.pone.0211392
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of personal laser scanning in forestry inventory

Abstract: Light Detection and Ranging (LiDAR) technology has been widely used in forestry surveys in the form of airborne laser scanning (ALS), terrestrial laser scanning (TLS), and mobile laser scanning (MLS). The acquisition of important basic tree parameters (e.g., diameter at breast height and tree position) in forest inventory did not solve the problem of low measurement efficiency or weak GNSS signal under the canopy. A personal laser scanning (PLS) device combined with SLAM technology provides an effective soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 46 publications
6
127
0
Order By: Relevance
“…However, the lower parts of a tree crown with many pendulous branches caused by self-weighting will disrupt the uniform shape. Trunk knots or twigs originating from a trunk will result in horizontal cross sections of trunks without well-defined circle shapes, which will complicate the location of trunks based on circle-detection algorithms such as Hough transform [48] or cylinder fitting [49]. Meanwhile, the accuracy of trunk detection algorithms based on MLS and TLS data would markedly decrease when understory vegetation is present in the forest plot, which results in the generation of much more occlusion.…”
Section: The Advantages Of Our Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lower parts of a tree crown with many pendulous branches caused by self-weighting will disrupt the uniform shape. Trunk knots or twigs originating from a trunk will result in horizontal cross sections of trunks without well-defined circle shapes, which will complicate the location of trunks based on circle-detection algorithms such as Hough transform [48] or cylinder fitting [49]. Meanwhile, the accuracy of trunk detection algorithms based on MLS and TLS data would markedly decrease when understory vegetation is present in the forest plot, which results in the generation of much more occlusion.…”
Section: The Advantages Of Our Approachmentioning
confidence: 99%
“…Different from the traditional methods based on computer graphics or image processing techniques [49,50], Faster R-CNN utilises a large number of data samples to extract the semantic features of the detection target and automatically recognise the tree trunk in the deep images. As the number of training samples of tree trunks increases and the capacity of the deep learning network continues to improve, a deep learning-based algorithm with robustness, generality and scalability will appear for detecting tree trunks of different tree species and under different plot site conditions according to the framework of our algorithm concept.…”
Section: The Advantages Of Our Approachmentioning
confidence: 99%
“…Of all the forest parameters that can be obtained through nondestructive in-situ measurements, the diameter of the breast height (DBH, 1.30 m height) not only helps researchers understand the structure of a forest but also reflects forest growth state. It contributes to aboveground forest biomass estimation and bridges empirical and process-based models, which directly inform global carbon cycling models [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This technology has the ability to generate high spatial resolution and accurate three-dimensional (3D) point cloud data. Consequently, it has been widely applied in forestry surveys to acquire basic tree parameters [16], as well as estimate AGB and carbon storage [17,18]. ALS can produce large-scale 3D point cloud data in a short time, from which tree height, DBH, canopy height and density metrics can be obtained, and then the AGB of trees can be evaluated.…”
mentioning
confidence: 99%
“…However, this method of assessing the biomass by ALS is prone to problems, including large estimation uncertainties, large costs, and limited information [21,22]. The system's performance is compromised in forest areas with weak GNSS signals or large variations of topography [16,23]. TLS can generate detailed and accurate parameter information of the 3D structure of trees by calculating the time difference between the emission and return of laser pulses and analyzing the energy of the returned laser pulses, which is not affected by GNSS signals and offers opportunities for a consistent and robust framework to support AGB estimates [3,24].Terrestrial laser scanning (TLS) has shown great potential for accurately assessing forest biomass with greater precision than inferred from the nationwide allometric biomass models [8,25].…”
mentioning
confidence: 99%